The Impact of Social Media Use on Gen Z Mental Health: The Relationship Between FOMO and Social Anxiety - Larisu, Zulfiah (Psikologiya Journal, 2024)
This study examines the relationship between Fear of Missing Out (FOMO), social anxiety, and the impact of social media use on Generation Z's mental health. Using a descriptive quantitative approach, the study involved 300 respondents aged 16-25 who were surveyed through an online questionnaire. The analysis showed that the more intensive the use of social media, the higher the level of FOMO and social anxiety experienced by Generation Z. Social media, designed to connect individuals, often creates the illusion of superficial relationships and increases social pressure. The research also revealed that algorithms tailored to user preferences contribute to unhealthy social comparisons, thus exacerbating feelings of not being good enough and social isolation. These findings emphasize the importance of managing social media use wisely and developing digital literacy programs aimed at raising awareness of possible negative impacts on mental health.